Students' perceptions and outcome of teacher feedback: a systematic review - Christian Brandmo; Siv M. Gamlem (Frontiers in Education)
This systematic review examines students' perceptions and outcomes of teacher feedback in elementary and lower secondary education (ages 10–16). The study explores how different feedback types and personal and relational factors influence students' achievement and their cognitive, emotional, and behavioral outcomes. Following PRISMA guidelines and the PICO framework, 96 empirical studies were analyzed, focusing on feedback-related student outcomes and moderating factors. Findings indicate that high-quality, tailored, and action-oriented feedback positively affects student achievement, motivation, and engagement, while negative or vague feedback can lead to demotivation and avoidance behaviors. Students prefer direct and individualized feedback, and trust in the teacher-student relationship is crucial for effective feedback uptake. Social dynamics, gender differences, and feedback interpretation influence student outcomes, emphasizing the need for adaptive feedback strategies. The review suggests that future research should focus on finding specialities and commonalities across various groups as well as on integrating AI with human feedback systems.